Moisture Diffusivity Coefficient and Convective Drying Modelling of Murta (Ugni Molinae Turcz): Influence of Temperature and Vacuum on Drying Kinetics - Lemus-Mondaca, R (2013)
In this study, murta (Ugni molinae Turcz) or murtilla berries were dried in single layer at air temperatures of 50, 60 and 70 °C under vacuum and atmospheric pressure conditions. The effect of drying air temperature and vacuum on the basic dehydration characteristics of murta was determined. For the kinetic modelling, ten mathematical expressions were fitted to the experimental data. Kinetic parameters and diffusion coefficients as evaluated by an Arrhenius-type equation, showed temperature dependency. Fick s second law was used to calculate the effective moisture diffusivity that varied from 3.10 to 11.27 × 10-10 m2/s and from 5.50 to 11.30 × 10-10 m2/s with activation energy values of 59.27 and 34.30 kJ/mol for atmospheric pressure and vacuum drying, respectively. According to the statistical tests applied, the Midilli-Ku uk model obtained the best-fit quality on experimental data, followed closely by the Weibull distribution model, the Page and the modified Page models. © 2011 Springer Science+Business Media, LLC.